Relationship between atopic dermatitis, depression and anxiety: a two‐sample Mendelian randomization study. (31st May 2021) - Baurecht, H.; Welker, C.; Baumeister, S.‐E.; Weidnger, S.; Meisinger, C.; Leitzmann, M.F.; Emmert, H.
Summary: Background: Growing evidence suggests that atopic dermatitis (AD) is associated with an increased risk of depressive disorders and anxiety. However, existing studies were observational and may have uncovered correlations but could not easily disentangle noncausal or reverse‐causal associations because these associations could be confounded and may not reflect true causal relationships. Objectives: To examine, in a two‐sample Mendelian randomization study, the potential effect of AD on the risk of depressive disorders and anxiety. Methods: Genetic instruments from the largest available genome‐wide association study (GWAS) for AD (10 788 cases and 30 047 controls) were used to investigate the relationship to broad depression (170 756 cases and 329 443 controls), major depressive disorder (MDD; 30 603 cases and 143 916 controls) and anxiety (5580 cases and 11 730 controls). A set of complementary approaches were carried out to assess horizontal pleiotropy and related potential caveats occurring in MR studies. Results: We observed no causal impact of AD on the risk of depressive disorders and anxiety, with close‐to‐zero effect estimates. The inverse weighted method revealed no associations of AD on broad depression [odds ratio (OR) 1·014; P  = 0·431], probable MDD (OR 1·002; P  = 0·568), International Classification of Diseases, Ninth/Tenth Revision‐based MDD (OR 1·001; P  = 0·466) or anxiety (OR 1·097; P  = 0·180). Conclusions: This MR study does not support a causal effect of AD on depression and anxiety. Abstract : What is already known about this topic? There is growing evidence that atopic dermatitis (AD) is related to depressive disorders and anxiety. Observational studies are prone to reverse causation and confounding, distorting true relationships. Observational study results are inconclusive regarding the effect of AD on depression and anxiety. What does this study add? Using Mendelian randomization as an alternative approach to investigate causality, we did not find a causal relationship between AD and depressive disorders or anxiety. Linked Comment:  M. Standl. Br J Dermatol 2021; 185 :694–695 .